The importance of growth kinetic analysis in determining bacterial susceptibility against antibiotics and silver nanoparticles - Theophel, Karsten; Schacht, Veronika J.; Schlüter, Michael; Schnell, Sylvia; Stingu, Catalina-Suzana; Schaumann, Reiner; Bunge, Michael (Frontiers in Microbiology, 2014)
Routine antibiotics susceptibility testing still relies on standardized cultivation-based analyses, including measurement of inhibition zones in conventional agar diffusion tests and endpoint turbidity-based measurements. Here, we demonstrate that common off-line monitoring and endpoint determination after 18–24 h could be insufficient for reliable growth-dependent evaluation of antibiotic susceptibility. Different minimal inhibitory concentrations were obtained in 20- and 48-h microdilution plate tests using an Enterococcus faecium clinical isolate (strain UKI-MB07) as a model organism. Hence, we used an on-line kinetic assay for simultaneous cultivation and time-resolved growth analysis in a 96-well format instead of off-line susceptibility testing. Growth of the Enterococcus test organism was delayed up to 30 h in the presence of 0.25 µg mL-1 of vancomycin and 8 µg mL-1 of fosfomycin, after which pronounced growth was observed. Despite the delayed onset of growth, treatment with fosfomycin, daptomycin, fusidic acid, cefoxitin, or gentamicin resulted in higher maximum growth rates and/or higher final optical density values compared with antibiotic-free controls, indicating that growth stimulation and hormetic effects may occur with extended exposure to sublethal antibiotic concentrations. Whereas neither maximum growth rate nor final cell density correlated with antibiotic concentration, the lag phase duration for some antibiotics was a more meaningful indicator of dose-dependent growth inhibition. Our results also reveal that non-temporal growth profiles are only of limited value for cultivation-based antimicrobial silver nanoparticle susceptibility testing. The exposure to Ag(0) nanoparticles led to plasma membrane damage in a concentration-dependent manner and induced oxidative stress in Enterococcus faecium UKI-MB07, as shown by intracellular ROS accumulation.